2015
DOI: 10.3389/fmicb.2015.00432
|View full text |Cite
|
Sign up to set email alerts
|

Increased seawater temperature increases the abundance and alters the structure of natural Vibrio populations associated with the coral Pocillopora damicornis

Abstract: Rising seawater temperature associated with global climate change is a significant threat to coral health and is linked to increasing coral disease and pathogen-related bleaching events. We performed heat stress experiments with the coral Pocillopora damicornis, where temperature was increased to 31°C, consistent with the 2–3°C predicted increase in summer sea surface maxima. 16S rRNA amplicon sequencing revealed a large shift in the composition of the bacterial community at 31°C, with a notable increase in Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 93 publications
7
122
3
1
Order By: Relevance
“…The marine environment is a heterogeneous landscape at the microscale and a bacterium's ability to accurately navigate gradients of nutrients and infochemicals may provide it with a competitive advantage (Taylor and Stocker 2012). Chemotaxis is found governing bacteria − phytoplankton interactions (Bell and Mitchell 1972;Blackburn et al, 1998;Stocker and Seymour 2012), facilitating symbioses such as that between Vibrio fischeri and squid (Mandel et al, 2012), implicated in the onset of disease (Otoole et al, 1996;Banin et al, 2001;Rosenberg and Falkovitz 2004;Larsen et al, 2004;Meron et al, 2009) and common throughout coral reefs (Tout et al, 2015b). Within this framework, reef-building corals are becoming a focal system for studying the role of motility in bacteria-host interactions in the ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine environment is a heterogeneous landscape at the microscale and a bacterium's ability to accurately navigate gradients of nutrients and infochemicals may provide it with a competitive advantage (Taylor and Stocker 2012). Chemotaxis is found governing bacteria − phytoplankton interactions (Bell and Mitchell 1972;Blackburn et al, 1998;Stocker and Seymour 2012), facilitating symbioses such as that between Vibrio fischeri and squid (Mandel et al, 2012), implicated in the onset of disease (Otoole et al, 1996;Banin et al, 2001;Rosenberg and Falkovitz 2004;Larsen et al, 2004;Meron et al, 2009) and common throughout coral reefs (Tout et al, 2015b). Within this framework, reef-building corals are becoming a focal system for studying the role of motility in bacteria-host interactions in the ocean.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacterium Vibrio shiloi causes only slow partial bleaching at 23°C, but rapid and severe bleaching at 29°C in the Mediterranean coral Oculina patagonica (Toren et al, 1998;Banin et al, 2001). Similarly, the globally distributed bacterial pathogen Vibrio coralliilyticus (Pollock et al, 2010) causes rapid tissue lysis of its coral host, Pocillopora damicornis, when temperatures exceed 26°C (Ben-Haim and Rosenberg 2002;Ben-Haim et al, 2003) and is more abundant in heat-stressed corals (Tout et al, 2015b), whereas increases in Caribbean Yellow Band Disease between 1998 and 2010 have been associated with elevated winter seawater temperatures (Burge et al, 2014;Weil et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during a bleaching event in Australia, the coral microbiome showed an increase in genes associated with virulence factors (Littman et al, 2011). Correspondingly, during heat stress experiments, the known pathogen V. coralliilyticus increased in abundance by four orders of magnitude (Tout et al, 2015). One likely mechanism for these observed changes are strong competition between native commensals and pathogenic bacteria (i.e., V. shiloi and V. coralliilyticus) on corals, with temperature stress mediating the growth of the foreigners.…”
Section: Stressors Increase Opportunistic and Pathogenic Bacterial Tamentioning
confidence: 99%
“…In comparison, a meta-analysis of 16S sequences from 32 papers, showed that the microbiome of bleached corals differed from that of healthy corals primarily in having a higher proportion of two specific taxa: Vibrios and Acidobacterias (Mouchka et al, 2010). An increase in Vibrionales under climate change stress is unsurprising as the cultivable Vibrio strain AK-1 was shown to induce coral bleaching (Kushmaro et al, 1998) (albeit the coral, Oculina patagonica, may have developed resistance to this bacteria; Mills et al, 2013) and Vibronales are a common taxa to increase under conditions of thermal stress (Bourne et al, 2007;Frydenborg et al, 2013;Tout et al, 2015). Importantly, the coral microbiome may have a temperature tolerance threshold, as it was found that bacterial community structure only changes after an elevation of temperature greater than 1 • C; all exposures at temperatures lower than this threshold showed no evidence of community alterations (Salerno et al, 2011).…”
Section: Stressors Increase Opportunistic and Pathogenic Bacterial Tamentioning
confidence: 99%
“…This increase in epizootics is likely due in part to changes in marine bacterial-animal relationships as a result of anthropogenic inputs and the changing climate. Coastal marine ecosystems and the surrounding seawater are increasingly saturated with microbes profiting from rising temperatures (Tout et al 2015;Zaneveld et al 2016) and increased available nutrients due to both agricultural run-off (Garren and Azam 2012) and a shift to algal-dominated ecosystems (Haas et al 2016). This increase in microbial abundance coupled with behavioral and gene-regulatory changes in previously benign bacteria has altered definitions of disease and symbiosis.…”
Section: Introductionmentioning
confidence: 99%